Protein Spin Labeling with a Photocaged Nitroxide Using Diels–Alder Chemistry - Kugele, Anandi (John Wiley and Sons Inc., 2019)

(untitled) (Chembiochem)
EPR spectroscopy of diamagnetic bio‐macromolecules is based on site‐directed spin labeling (SDSL). Herein, a novel labeling strategy for proteins is presented. A nitroxide‐based spin label has been developed and synthesized that can be ligated to proteins by an inverse‐electron‐demand Diels–Alder (DA(inv)) cycloaddition to genetically encoded noncanonical amino acids. The nitroxide moiety is shielded by a photoremovable protecting group with an attached tetra(ethylene glycol) unit to achieve water solubility. SDSL is demonstrated on two model proteins with the photoactivatable nitroxide for DA(inv) reaction (PaNDA) label. The strategy features high reaction rates, combined with high selectivity, and the possibility to deprotect the nitroxide in Escherichia coli lysate.